Prevalence of malocclusion in the schools of the District of Tacares, Grecia. 2011 - Campos Arias, Flor de María (2014)
This epidemiological study focuses on the prevalence of malocclusion in schools of the Tacares District, Grecia, Costa Rica 2011. Its objective was to measure such occurrence in first-grade children. A data questionnaire was used to gather sociodemographic and clinical information. The first came from parents and the second of 88 children, whose average age was 7.01 years. Most relevant results found that: the most frequent oral habits were the use of a bottle (66%), thumb sucking (19%) and the use of pacifier (10%). 10.2% of children presented protractile tongue. 22.7% showed proximal caries. Premature loss of teeth was prevention 22.7%. Teeth with caries were found in 15 per cent. 54.5% presented proportional facial vertical segments, 42% showed an increased lower third and 58% decreased lower third. 48.9% showed overcrowding of teeth. 52.3% introduced asymmetric dental arches. 10.1% of students presented posterior crossbite, with predominance of the unilateral right. The alteration in Angle ́s molar classification accounted for 10.2% with the pattern of Class II and 11.3% to the class III pattern. There were anterior crossbite in 19.3%. These results will be used to implement a program for promoting oral health, prevention of malocclusion in earlier ages and timely care. This would extend to long-term community orthodontic coverage, since the early attention of some risk factors, prevent interceptive orthodontic treatments that demand greater economic investment, in time and human resources.